Olive Leaf: From Tradition to Clinic - Ghazaleh Mosleh; Abdolali Mohagheghzadeh; Pouya Faridi (Shiraz University of Medical Sciences, 2016)
The olive (Olea europaea from the Oleaceae family) leaves have had a lot of medicinal usages in traditional and modern medicine. In traditional Iranian medicine (TIM), it has special indications for wound healing and skin applications such as antiperspirant applications, and also its ash is used in ophthalmic traditional remedies. Literature survey was performed via electronic search on Pubmed, Scopus and Siencedirect. We found 270 articles related to the topic. Conventional pharmacy texts including Martindale, British pharmacopoeia and Lexi natural products as well as TIM texts were reviewed. Our results showed that Olive leaf has responsible effects such as antioxidant, antitoxic and anticancer properties. Also it has antimicrobial and antiviral effects as well as effects on nervous system, endocrine system, gastrointestinal system and cardiovascular system. It has therapeutic effects on some metabolic disorders and cutaneous complications and some miscellaneous effects such as anti-arthritis and anti-bone loss effects. Despite the large amount of studies on the possible effects of olive leaf has been done, the number of available products and their therapeutic targets are limited. It is expected that more extensive studies done on the olive leaf in clinical trials and according to its dose adjustment and special cautions, it becomes more popular herbal medicine in markets and clinics.